Tracing the Red Thread: Chinese-U.S. Transnational Adoption and the Legacies of "Home" - Cohen, Frayda (Anthropologica, 2015)
Contemporary forms of globalization have expanded conceptions of "family." A particular instance of this involves U.S. parents travelling to adopt children from China. These families utilize transnational networks in ways that encourage multiple trips "home" to China and may involve heritage tours, humanitarian projects or nascent birth-parent searches. Consequently, adoption tourism, marketed as an "adventurous family journey" to a "far away world" where your "cherished gift" awaits, illustrates the ways in which contemporary notions of kinship are linked to complex forms of travel whereby boundaries between tourism, leisure and social projects are increasingly blurred.